Targeting of the Eukaryotic Translation Initiation Factor 4A Against Breast Cancer Stemness - Sridharan, Sangita; Robeson, Megan; Bastihalli-Tukaramrao, Diwakar; Howard, Cory M.; Subramaniyan, Boopathi; Tilley, Augustus M. C.; Tiwari, Amit K.; Raman, Dayanidhi (Frontiers in Oncology, 2019)
Breast cancer stem cells (BCSCs) are intrinsically chemoresistant and capable of self-renewal. Following chemotherapy, the minimal residual disease can develop due to BCSCs which can repopulate into a relapsed tumor. Therefore, it is imperative to co-target BCSCs along with the bulk tumor cells to achieve therapeutic success and prevent recurrence. So, it is vital to identify actionable molecular targets against both BCSCs and bulk tumor cells. Previous findings from our lab and others have demonstrated that inhibition of the emerging drug target eIF4A with Rocaglamide A (RocA) was effective in killing triple-negative breast cancer cells (TNBC). RocA specifically targets the pool of eIF4A bound to the oncogenic mRNAs that requires its helicase activity for their translation. This property enables specific targeting of tumor cells. In this study, we postulated that eIF4A could be a vulnerable node in BCSCs. In order to test this, we generated a paclitaxel-resistant TNBC cell line which demonstrated an elevated level of eIF4A along with increased levels of cancer stemness markers (ALDH activity and CD44), pluripotency transcription factors (SOX2, OCT4 and Nanog) and drug transporters (ABCB1, ABCG2, and ABCC1). Furthermore, genetic ablation of eIF4A resulted in reduced expression of ALDH1A1, pluripotency transcription factors and key drug transporters. This pointed out that eIF4A is likely associated with selected proteins that are critical to BCSCs, and hence targeting eIF4A may eliminate BCSCs. Therefore, we isolated BCSCs from two TNBC cell lines: MDA-Bone-Un and SUM-159PT. Following RocA treatment, the self-renewal ability of the BCSCs was significantly reduced as determined by the efficiency of the formation of primary and secondary mammospheres. This was accompanied by a reduction in the levels of Nanog, OCT4 and drug transporters. Exposure to RocA also induced cell death of the BCSCs as evaluated by DRAQ7 and cell viability assays. The induction of cleaved caspase-3 following RocA treatment indicated cell death by apoptosis. Overall, we identified that RocA could be an effective drug in targeting BCSCs and eIF4A is an actionable molecular target in both BCSCs and bulk tumor cells. Anti-eIF4A inhibitors can be effectively combined with existing chemo-, radio- and/or immunotherapies to achieve therapeutic synergy.